A different paradigm for the initial colonisation of Sahul. Issue 1 (17th January 2020) - ALLEN, JIM; O'CONNELL, JAMES F.
ABSTRACT: The questions of when and how humans reached Sahul, the Pleistocene continent of Australia and New Guinea, has remained a central issue of Australian archaeology since its development as an academic discipline in the mid‐twentieth century. Modelling this event has persistently appealed to minimal assumptions – the simplest watercraft, the shortest routes, the smallest viable colonising groups. This paper argues that Australian archaeology can no longer ignore the way our understanding of this initial colonisation is being reshaped by current genomic research. It reviews this evidence and concludes that a colonising wave of hundreds or perhaps low thousands of people was involved. If correct, it suggests that we need to rethink our models, modify or discard the minimalist assumptions that have so far driven them and consider how this different paradigm affects our understanding of early settlement in Sahul. Abstract : The questions of when and how humans reached Sahul, the Pleistocene continent of Australia and New Guinea, has remained a central issue of Australian archaeology since its development as an academic discipline in the mid‐twentieth century. Modelling this event has persistently appealed to minimal assumptions – the simplest watercraft, the shortest routes, the smallest viable colonising groups. This paper argues that Australian archaeology can no longer ignore the way our understanding of this initial colonisation is being reshaped by current genomic research. It reviews this evidence and concludes that a colonising wave of hundreds or perhaps low thousands of people was involved. If correct, it suggests that we need to rethink our models, modify or discard the minimalist assumptions that have so far driven them and consider how this different paradigm affects our understanding of early settlement in Sahul. Résumé: La question de savoir quand et comment les hommes ont atteint Sahul, le continent pléistocène regroupant l'Australie et la Nouvelle‐Guinée, persiste comme une problématique centrale de l'archéologie australienne depuis son essor en tant que discipline universitaire au milieu du vingtième siècle. La modélisation de cet événement s'est appuyée de façon récurrente sur des présupposés minimalistes, impliquant les moyens de navigation les plus simples, les routes les plus courtes, les groupes de colonisation viable les plus restreints. Ce papier soutient que l'archéologie australienne ne peut plus ignorer combien notre compréhension de ce peuplement initial se trouve aujourd'hui redéfinie par la recherche génomique en cours. Il passe en revue les données et conclue que plusieurs centaines ou quelques milliers de personnes ont participé à cette vague de peuplement. Si cette hypothèse est correcte, elle implique que nous repensions nos modèles, que nous modifiions ou abandonnions les présupposés minimalistes qui ont jusqu'à présent défini ceux‐ci et que nous analysions comment ce nouveau paradigme influence notre compréhension du premier peuplement de Sahul.